Truncated (2/2) hemoglobin: Unconventional structures and functional roles in vivo and in human pathogenesis. (April 2022) - Nardini, Marco; Pesce, Alessandra; Bolognesi, Martino
Abstract: Truncated hemoglobins (trHbs) build a sub-class of the globin family, found in eubacteria, cyanobacteria, unicellular eukaryotes, and in higher plants; among these, selected human pathogens are found. The trHb fold is based on a 2/2 α-helical sandwich, consisting of a simplified and reduced-size version of the classical 3/3 α-helical sandwich of vertebrate and invertebrate globins. Phylogenetic analysis indicates that trHbs further branch into three groups: group I (or trHbN), group II (or trHbO), and group III (or trHbP), each group being characterized by specific structural features. Among these, a protein matrix tunnel, or a cavity system implicated in diatomic ligand diffusion through the protein matrix, is typical of group I and group II, respectively. In general, a highly intertwined network of hydrogen bonds stabilizes the heme bound ligand, despite variability of the heme distal residues in the different trHb groups. Notably, some organisms display genes from more than one trHb group, suggesting that trHbN, trHbO, and trHbP may support different functions in vivo, such as detoxification of reactive nitrogen and oxygen species, respiration, oxygen storage/sensoring, thus aiding survival of an invading microorganism. Here, structural features and proposed functions of trHbs from human pathogens are reviewed. Highlights: The trHb fold is a subset of the classical globin fold, being characterized by a 2/2 α-helical sandwich. Phylogenetic analysis indicates that trHbs branch into three groups: I (N), II (O), and III (P). In trHbN and trHbO, diatomic ligand diffusion to the heme-iron occurs through protein matrix tunnels or cavity systems. Proposed trHb functions are deoxification of reactive nitrogen and oxygen species, respiration, oxygen storage/sensoring. TrHbs help the survival of selected human pathogens in vivo.